2021
DOI: 10.5829/ije.2021.34.08b.14
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening of RC Beams Using SCC Jacket Consisting of Glass Fiber and Fiber-Silica Fume Composite Gel

Abstract: In this paper, strengthening of RC beams with self-consolodating concrete (SCC) jacket containing glass fiber (GF) and fiber-silica fume composite gel (FSCG) were investigated. FSCG can use as a substitute for a part of the cement that contains silica fume powder, polypropylene fibers, superplasticizer, concrete waterproof, and some other admixtures. In order to evaluate the performance of the proposed jacket, twelve beams were strengthened and a control beam was made. The variables included the amount of glas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…Due to the importance of shear failure in reinforced concrete members which is happened suddenly without warning, Alferjani et al [11] and Abdollahi et al [12] presented the experimental and analytical studies for reinforced concrete members to evaluate the shear capacity. Rahmani et al [13], Faez et al [14] and Mohsenzadeh et al [15] studied the reinforced concrete beams strengthening due to the importance of this topic.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the importance of shear failure in reinforced concrete members which is happened suddenly without warning, Alferjani et al [11] and Abdollahi et al [12] presented the experimental and analytical studies for reinforced concrete members to evaluate the shear capacity. Rahmani et al [13], Faez et al [14] and Mohsenzadeh et al [15] studied the reinforced concrete beams strengthening due to the importance of this topic.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have considered the strengthening of RC beams in recent years [9][10][11][12]. Attar et al [13] investigated the strengthened RC beams with self-compacting concrete (SCC) jackets containing fibers.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that RC jackets containing aluminum nanoparticles, depending on the thickness jacket, the number of rebars used in the jackets, and the length of the beam span, have increased the flexural strength by 155 to 447% [11]. Mohsenzadeh et al [12] investigated the strengthened RC beams using SCC jacket containing glass fiber and fibrous silica fume gel (FSFG). Concrete jackets containing glass fiber and FSCG, depending on the amount of glass fiber, have increased the energy absorption capacity of the beams by about 89 to 463%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that the proposed method could increase the shear capacity of the damaged beam by about 27%. Mohsenzadeh et al [9] evaluated the behavior of RC beams with RC jackets containing glass fibers and micro silica gel. The results of the tests indicated that the proposed jackets could increase the energy absorption capacity by about four times.…”
Section: Introductionmentioning
confidence: 99%